Effects of the unity vacuum suspension system on transtibial gait for simulated non-level surfaces. - Gabrielle Thibault; Hossein Gholizadeh; Emily Sinitski; Natalie Baddour; Edward D Lemaire (PLoS ONE)
Walking on various surfaces encountered in everyday life requires lower limb prosthesis users to continually adapt their movement patterns. Elevated vacuum suspension systems could improve transtibial amputee gait on non-level surfaces; however, research is lacking to guide clinical practice. Twelve transtibial amputees were fitted with the Össur sleeveless vacuum suspension system (Unity). After a one month accommodation period, the CAREN-Extended system was used to evaluate gait on a self-paced treadmill when walking with continuous perturbations (medial-lateral translations, rolling hills, simulated uneven ground) with an active or inactive vacuum suspension system. Significant differences between active and inactive vacuum conditions (p<0.05) were found for some temporal-spatial and kinematic gait parameters, but the differences were small and not considered clinically significant. Our findings suggest that potential vacuum pump failures would not immediately affect gait performance in a moderately high functioning amputee population. However, residual limb volume changes over time due to the removal of elevated vacuum may adversely affect socket fit, leading to greater gait differences and reduced quality of life.